A method for preparing super-amphiphobic porous powder and super-amphiphobic coating containing the powder
By preparing ultra-double porous powder and applying it to the coating, the problems of poor wear resistance of existing super-hydrophobic coatings and the hazards of organic solvents during the preparation process are solved, and the wear resistance and super-hydrophobicity of the coatings are significantly improved, while avoiding the use of harmful solvents.
Patent Information
- Application Number
- CN202310236470.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-03-13
AI Technical Summary
After physical or chemical damage, the surface hydrophobicity of the existing superhydrophobic coatings decreases or loses, and the organic solvents used in the preparation process cause harm to the human body and the environment.
A method of preparing a super double spore porous powder is adopted. By mixing surfactant, nanosol, ammonia and low-surface energy substances in a constant temperature water bath of 50 to 80°C, a modified nanoparticle suspension is formed, and then dried at high temperature to obtain super double spore porous powder loaded with nanoparticles. When the powder is formed in the coating, the nanoparticles are loaded in the pores of the microporous particles, ensuring the wear resistance and superhydrophobicity of the coating.
The wear resistance and long-term effectiveness of the superhydrophobic coating is significantly improved, and when the coating is worn, the release of nanoparticles maintains the superhydrophobicity of the coating without the use of harmful organic solvents.
Smart Images

Figure CN116814110B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a super-amphiphobic porous powder and also relates to a coating containing the super-amphiphobic porous powder. Background Art
[0002] Super-hydrophobic surfaces have important application prospects in many fields such as self-cleaning, anti-corrosion, anti-icing, anti-fog, anti-corrosion and oil-water separation due to their special surface wettability. In the real environment, solid surfaces will not only come into contact with water, but also with oils such as soybean oil, n-hexane and carbon tetrachloride. These oily liquids are easy to spread on the hydrophobic surface, limiting the use of super-hydrophobic coatings in oily environments. Therefore, in order to meet the needs of practical applications, it is urgent to develop a super-amphiphobic coating to solve the self-cleaning problem in an environment where oil and water coexist. Super-amphiphobic surfaces refer to surfaces with contact angles of water and oil droplets greater than 150° under the synergistic effect of surface micro-nanostructures and low surface energy substances, and have excellent comprehensive properties such as three-proof (waterproof, oil-proof, dust-proof), anti-dew, drag reduction, and corrosion resistance. They can be widely used in industrial fields such as three-proof fabrics, anti-dew and anti-frost of air conditioners, antibacterial and mildew-proof building materials, oil-water separation, anti-adhesion interfaces, and water collection systems.
[0003] However, when the fragile micro-nanostructure on the surface of the super-hydrophobic coating is physically or chemically damaged, its surface hydrophobicity decreases or is lost, and the poor wear resistance limits its use in actual working conditions. In the process of preparing super-hydrophobic coatings, organic solvents such as ethanol and acetone are added, which can cause great harm to the human body and the environment. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a super-amphiphobic porous powder, and also to provide a coating containing the super-amphiphobic porous powder. The super-amphiphobic porous powder prepared by the method can be applied to various resin systems to form coatings, so that the wear resistance of the final super-amphiphobic coating is significantly improved, and when the coating is worn, the nanoparticles in the super-amphiphobic porous powder are instantly released so that the super-hydrophobicity of the coating continues to be maintained, thereby effectively improving the long-term effectiveness of the super-hydrophobic and super-oleophobic coating.
[0005] Technical solution: The method for preparing the super-amphiphobic porous powder of the present invention comprises the following steps:
[0006] (1) adding 0.3-0.5 parts of a surfactant, 5-8 parts of a nanosol, 4-5 parts of ammonia water, and 0.4-0.5 parts of a low surface energy substance to water in a constant temperature water bath at 50-80° C., and stirring to obtain a modified nanoparticle suspension;
[0007] (2) adding 0.5 to 0.6 parts of a low surface energy substance, 0.7 to 1.2 parts of aluminum hydroxide and 3 to 5 parts of micron porous particles to the nanoparticle suspension in sequence, and stirring to obtain a micron porous particle suspension loaded with nanoparticles;
[0008] (3) The micron porous particle suspension is dried at high temperature to obtain a super-amphiphobic porous powder loaded with nanoparticles.
[0009] Wherein, in step (1), the surfactant is at least one of FS-3100, FS-61 or FS-30.
[0010] Wherein, in step (1), the nanosol is one of zinc oxide, silicon dioxide and titanium dioxide with a particle size of 5 to 40 nm, the solid content of the nanosol is 10 wt.% to 35 wt.%, and the pH value is 9 to 12. Ammonia water is used to keep the reaction system alkaline and promote the breaking of Si-O-Si bonds in low surface energy substances, thereby grafting them onto micron porous particles.
[0011] Wherein, in step (1) and step (2), the low surface energy substance is at least one of tridecafluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, tridecafluorooctyltrimethoxysilane or heptadecafluorodecyltriethoxy.
[0012] Wherein, in step (2), the micron porous particles are at least one of ceramic, diatomaceous earth or glass porous microspheres with a particle size of 10 to 50 μm, and the micron porous particles are in the shape of flakes, columns, discs or spheres.
[0013] Wherein, in step (2), the solid content of the micron porous particle suspension loaded with nanoparticles is 1wt.% to 30wt.%, and the pH value is 9 to 12.
[0014] Wherein, in step (3), the drying temperature is 120-180° C., and the drying time is 4-6 hours; the high temperature causes the surfactant in the solution to evaporate, thereby effectively preventing the surfactant from affecting the super-amphiphobic state of the super-amphiphobic porous powder.
[0015] Wherein, in step (3), the particle size of the super-amphiphobic porous powder loaded with nanoparticles is 10 to 80 μm.
[0016] The water-based coating containing the super-amphiphobic porous powder comprises the following components in parts by weight: 1.5 to 2 parts of super-amphiphobic porous powder, 0.15 parts of surfactant, 3 to 5 parts of film-forming material and 9 to 10 parts of deionized water.
[0017] The oily paint containing the super-amphiphobic porous powder comprises the following components in parts by weight: 0.1 to 0.5 parts of the super-amphiphobic porous powder, 0.5 to 0.6 parts of the oily resin, 0.15 to 0.2 parts of the curing agent and 1 to 2 parts of the organic solvent.
[0018] Among them, the volatile organic solvent is at least one of butyl acetate, ethanol, n-hexane, ether, benzene or ketones; the film-forming material is at least one of low surface energy water-based fluorocarbon resin, water-based acrylic resin or water-based polyurethane resin, silicone resin or epoxy resin; the curing agent is at least one of imidazoles, polyamides, aromatic amines, polyether amines, alicyclic amines or isocyanates.
[0019] The super-amphiphobic or oily coating is applied to any cleaned substrate surface by spraying, dipping, brushing or rolling, and then heated and dried in an oven at 80-200°C for 1-2 hours to obtain a super-amphiphobic coating. The contact angle of the super-amphiphobic coating in 5μL soybean oil can reach more than 165°, and the rolling angle is less than 2°.
[0020] The powder coating containing the super-amphiphobic porous powder comprises the following components in parts by mass: 0.2 to 1 part of the super-amphiphobic porous powder and 6 to 30 parts of the binder powder.
[0021] Wherein, the adhesive powder is at least one of polyester resin powder, polymethyl methacrylate powder or polytetrafluoroethylene resin powder.
[0022] 0.2 to 1 parts of super-amphiphobic porous powder and 6 to 30 parts of binder powder are placed in a multifunctional crusher to mix and stir the powder for 1 to 2 minutes to obtain a uniformly mixed powder; the uniformly mixed powder is electrostatically sprayed onto a metal substrate, placed in an oven and baked at 100 to 150° C. for 30 minutes, and high-temperature cured at 225° C. for 10 to 20 minutes, and then cooled to room temperature to obtain a super-amphiphobic coating.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The present invention adds aluminum hydroxide during the hydrophobic modification of micron porous particles. Aluminum hydroxide can increase the chemical bond activity of the micron porous particles (the activity of aluminum hydroxyl is greater than that of silicon hydroxyl), thereby effectively increasing the grafting rate of the micron porous particles to the hydrophobic groups, and at the same time increasing the bonding strength between the micron porous particles and the nanoparticles and the subsequent organic resin, thereby effectively improving the amphiphobicity (hydrophobicity and oleophobicity) of the super-amphiphobic porous powder and also effectively improving the strength and wear resistance of the coating. (2) In the super-amphiphobic porous powder of the present invention, nanoparticles are loaded in the pores of micron porous particles, the nanoparticles are completely hydrophobic modified, while the micron porous particles are incompletely hydrophobic modified, and the incompletely modified micron porous particles are rich in hydroxyl groups, which bridge the nanoparticles and the organic resin through chemical bonding, thereby improving the wear resistance of the coating itself and the bonding strength with the substrate; (4) The super-amphiphobic coating obtained based on the super-amphiphobic porous powder of the present invention can effectively improve the oil resistance and corrosion resistance of the substrate, and can also give the surface excellent anti-condensation, anti-icing and anti-frost properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Transmission electron microscope images of micron porous particles; (a) TEM image of micron porous particles loaded with Al(OH)3; (b) TEM image of micron porous particles not loaded with Al(OH)3;
[0025] Figure 2 DSC-TG curves of DE@SiO2 and DE@Al(OH)3; (a) DSC-TG curve of DE@SiO2 / Al(OH)3; (b) DSC-TG curve of DE@SiO2;
[0026] Figure 3 The hardness and elastic modulus of the modified micron porous powder, nano-silica loaded porous powder and super-amphiphobic porous powder obtained in Comparative Example 3, Comparative Example 4 and Example 3; (the abscissa in the figure represents the three powders of modified micron porous powder, nano-silica loaded porous powder and super-amphiphobic porous powder, the red line in the figure represents the elastic modulus, the right ordinate has been marked, the black line represents the hardness, and the left ordinate has been marked);
[0027] Figure 4 The tensile strength and elongation of coatings in different systems;
[0028] Figure 5 A physical picture of a porous particle suspension loaded with nanoparticles;
[0029] Figure 6Characterization of the wettability of several powders; (a) from left to right, unmodified aluminum hydroxide nanoparticles, unmodified micron porous particles and the state of the super-amphiphobic porous powder surface dyed with soybean oil prepared in Example 3; (b) is the water wettability of the super-amphiphobic porous powder prepared in Example 3;
[0030] Figure 7 The hydrophobicity and Cassie state diagram of the surface of the super-amphiphobic porous powder coating;
[0031] Figure 8 Optical photos and schematic diagrams of the surface of the super-amphiphobic porous powder coating after scribbling;
[0032] Fig. 9 The mechanical properties of the super-amphiphobic porous powder coating; (a) is the change of water wettability of the super-amphiphobic coating with wear cycles; (b) is a schematic diagram of the Taber wear test of the super-amphiphobic coating; (c) and (d) are SEM images of the super-amphiphobic coating before and after wear, respectively;
[0033] Fig.10 Schematic diagram of the super-amphiphobic coating before and after the pulling test; (a) is a schematic diagram before the pulling test; (b) is a schematic diagram after the pulling test;
[0034] Fig.11 The antifouling test of the super-amphiphobic coating; (a) is a schematic diagram before the antifouling test; (b) is a schematic diagram of cement slurry rolling off the coating; (c) is a schematic diagram of the cement slurry not contaminating the coating after the antifouling test;
[0035] Fig.12 The dustproof test of the super-amphiphobic coating; (a) is a schematic diagram before the dustproof test; (b) is a schematic diagram of the dust being washed away by water; (c) is a schematic diagram of the coating not contaminated by dust after the dustproof test;
[0036] Fig.13 Performance characterization of super-amphiphobic coating; (a) self-cleaning performance; (b) anti-fouling performance; (c) hydrophobicity and anti-concrete performance. DETAILED DESCRIPTION
[0037] Example 1
[0038] A method for preparing a porous powder loaded with aluminum hydroxide comprises the following steps:
[0039] (1) In a constant temperature water bath at 50° C., 5 parts of nanoparticles, 4 parts of ammonia water, 0.4 parts of perfluorodecyltriethoxysilane and 0.3 parts of a surfactant are sequentially added to 80 parts of deionized water, and magnetically stirred for 10 hours to obtain a modified nanoparticle suspension; the nanoparticles are aluminum hydroxide nanoparticles; the surfactant is a fluorocarbon surfactant FS-30;
[0040] (2) adding 0.6 parts of perfluorodecyltriethoxysilane and 3 parts of micron porous particles to the modified nanoparticle suspension in sequence, and stirring magnetically for 10 hours to obtain a porous particle suspension loaded with nanoparticles; the micron porous particles are diatomaceous earth;
[0041] (3) Drying the porous particle suspension loaded with nanoparticles at 180° C. for 4 hours to obtain a micron porous powder loaded with nanoparticles. The particle size of the micron porous powder loaded with nanoparticles is 20 to 30 μm.
[0042] Comparative Example 1
[0043] 3 parts of diatomaceous earth, 4 parts of ammonia water, 0.6 parts of perfluorodecyl triethoxysilane and 0.3 parts of fluorocarbon surfactant FS-30 were added to 80 parts of deionized water in a constant temperature water bath at 50°C, and magnetic stirring was performed for 10 hours to obtain a modified micron particle suspension; the modified micron particle suspension was dried at 180°C for 4 hours to obtain a micron porous powder without nanoparticles. The particle size of the micron porous powder without nanoparticles was 20 to 30 μm.
[0044] Figure 1 Transmission electron microscope image of micron porous particles. Figure 1 (a) It can be seen that a layer of aluminum hydroxide film is successfully loaded in the porous particles prepared in Example 1, and this translucent Al(OH)3 nanofilm is particularly obvious in the pores.
[0045] Example 2
[0046] The method for preparing the super-amphiphobic porous powder of the present invention comprises the following steps:
[0047] (1) In a constant temperature water bath at 50° C., 8 parts of silica sol, 4 parts of ammonia water, 0.4 parts of perfluorodecyl triethoxysilane and 0.3 parts of a surfactant are sequentially added to 80 parts of deionized water, and magnetically stirred for 10 hours to obtain a modified nanoparticle suspension; the nanoparticles are silicon dioxide nanoparticles; the surfactant is a fluorocarbon surfactant FS-30;
[0048] (2) adding 0.6 parts of perfluorodecyltriethoxysilane, 1.2 parts of aluminum hydroxide and 3 parts of micron porous particles to the modified nanoparticle suspension in sequence, and stirring magnetically for 10 hours to obtain a porous particle suspension loaded with nanoparticles; the micron porous particles are diatomaceous earth;
[0049] (3) Drying the porous particle suspension loaded with nanoparticles at 180° C. for 4 h to obtain micron porous powder DE@SiO2 / Al(OH)3 loaded with nanoparticles. The particle size of DE@SiO2 / Al(OH)3 is 20 to 30 μm.
[0050] Comparative Example 2
[0051] A method for preparing a super-amphiphobic porous powder comprises the following steps:
[0052] (1) In a constant temperature water bath at 50° C., 8 parts of silica sol, 4 parts of ammonia water, 0.4 parts of perfluorodecyl triethoxysilane and 0.3 parts of a surfactant are sequentially added to 80 parts of deionized water, and magnetically stirred for 10 hours to obtain a modified nanoparticle suspension; the nanoparticles are silicon dioxide nanoparticles; the surfactant is a fluorocarbon surfactant FS-30;
[0053] (2) adding 0.6 parts of perfluorodecyltriethoxysilane and 3 parts of micron porous particles to the modified nanoparticle suspension in sequence, and stirring magnetically for 10 hours to obtain a porous particle suspension loaded with nanoparticles; the micron porous particles are diatomaceous earth;
[0054] (3) Drying the porous particle suspension loaded with nanoparticles at 180° C. for 4 h to obtain micron porous powder DE@SiO2 loaded with nanoparticles. The particle size of DE@SiO2 is 20 to 30 μm.
[0055] Figure 2 The thermogravimetric analysis results of the two particles obtained in Example 2 and Comparative Example 2 are as follows: Figure 2 Thermogravimetric analysis shows that in DE@SiO2 and DE@SiO2 / Al(OH)3 systems, the mass change between 300 and 600°C represents the mass change of the grafted fluorosilane, where the mass of fluorosilane in the DE@SiO2 / Al(OH)3 system is 23.25%, and the mass of fluorosilane in the DE@SiO2 system is 16.69%, indicating that the grafting rate of fluorosilane in the DE@SiO2 / Al(OH)3 system is higher, so that the coating system with the addition of Al(OH)3 is more hydrophobic and oleophobic. After the addition of aluminum hydroxide, aluminum hydroxyl groups are formed, providing more grafting sites, so that more hydroxyl groups on the micron porous particles react with the low surface energy fluorosilane, increasing the grafting rate of the hydrophobic group, making the subsequent coating more hydrophobic, and more hydroxyl groups on the micron porous particles can react chemically with the hydroxyl groups on the resin and the substrate, enhancing the coating interface strength, thereby improving the wear resistance of the coating.
[0056] Example 3
[0057] The method for preparing the super-amphiphobic porous powder of the present invention comprises the following steps:
[0058] (1) In a constant temperature water bath at 50° C., 5 parts of silica sol, 4 parts of ammonia water, 0.4 parts of perfluorodecyltriethoxysilane and 0.3 parts of a surfactant are sequentially added to 80 parts of deionized water, and magnetically stirred for 10 hours to obtain a modified nanoparticle suspension; the nanoparticles are silicon dioxide nanoparticles; the surfactant is a fluorocarbon surfactant FS-30;
[0059] (2) adding 0.6 parts of perfluorodecyltriethoxysilane, 0.7 parts of aluminum hydroxide and 3 parts of micron porous particles to the modified nanoparticle suspension in sequence, and stirring magnetically for 10 hours to obtain a porous particle suspension loaded with nanoparticles; the micron porous particles are diatomaceous earth;
[0060] (3) Drying the porous particle suspension loaded with nanoparticles at 180° C. for 4 hours to obtain a micron porous powder loaded with nanoparticles. The particle size of the micron porous powder loaded with nanoparticles is 20 to 30 μm.
[0061] Comparative Example 3
[0062] In a constant temperature water bath at 50°C, 0.3 parts of fluorocarbon surfactant FS-30, 4 parts of ammonia water, 0.6 parts of perfluorodecyltriethoxysilane and 3 parts of diatomaceous earth were successively added to 80 parts of deionized water to prepare a micron porous particle suspension, which was then dried at 180°C for 4 hours to obtain a micron porous powder.
[0063] Comparative Example 4
[0064] (1) In a constant temperature water bath at 50° C., 5 parts of silica sol, 4 parts of ammonia water, 0.4 parts of perfluorodecyltriethoxysilane and 0.3 parts of a surfactant are sequentially added to 80 parts of deionized water, and magnetically stirred for 10 hours to obtain a modified nanoparticle suspension; the nanoparticles are silicon dioxide nanoparticles; the surfactant is a fluorocarbon surfactant FS-30;
[0065] (2) adding 0.6 parts of perfluorodecyltriethoxysilane and 3 parts of micron porous particles to the modified nanoparticle suspension, and stirring by magnetic force for 10 hours to obtain a porous particle suspension loaded with nano-silica; the micron porous particles are diatomaceous earth;
[0066] (3) Drying the porous particle suspension loaded with nano-silica at 180° C. for 4 h to obtain a porous powder loaded with nano-silica.
[0067] The hardness and elastic modulus of the modified micron porous powder, the porous powder loaded with nano-silica and the super-amphiphobic porous powder obtained in Comparative Example 3, Comparative Example 4 and Example 3 were tested and compared by nanoindentation test. The results are as follows: Figure 3 As shown, through Figure 3 It can be seen that the hardness and elastic modulus of the super-amphiphobic porous powder are better than those of the modified micron porous powder and the porous powder loaded with nano-silica, which is due to the addition of aluminum hydroxide.
[0068] Example 4
[0069] The coating was prepared using DE@SiO2 and DE@SiO2 / Al(OH)3 prepared in Example 2 as raw materials, specifically as follows:
[0070] In terms of mass fractions, 0.15 parts of fluorocarbon surfactant FS-30 and 1.5 parts of DE@SiO2 were dispersed in 9 parts of water, and then 3 parts of aqueous polyurethane resin were added and stirred for 5 minutes to obtain the coating of the porous powder. The porous powder coating was applied to the surface of any cleaned substrate, and heated and dried in an oven at 150°C for 1 hour to obtain a super amphiphobic coating of the DE@SiO2 system.
[0071] In terms of mass fractions, 0.15 parts of fluorocarbon surfactant FS-30 and 1.5 parts of DE@SiO2 / Al(OH)3 were dispersed in 9 parts of water, and then 3 parts of aqueous polyurethane resin were added. After stirring for 5 minutes, the porous powder coating was obtained. The porous powder coating was applied to any cleaned substrate surface, and heated and dried in an oven at 150°C for 1 hour to obtain a super amphiphobic coating of the DE@SiO2 / Al(OH)3 system.
[0072] Add 5 parts of pure polyurethane resin to 10 parts of deionized water to obtain a diluted polyurethane solution. Apply the diluted polyurethane solution to any cleaned substrate surface, place it in an oven at 150° C. for heating and drying for 1 hour to obtain a pure PU system coating.
[0073] The above three coating systems were subjected to tensile tests, and the results are as follows: Figure 4 As shown in the figure, the elongation of the super-amphiphobic coating of the DE@SiO2 / Al(OH)3 system is slightly lower than that of the super-amphiphobic coating of the DE@SiO2 system, while the tensile strength is as high as 155.68Mpa, which is 1.5 times that of the super-amphiphobic coating of the DE@SiO2 system. Compared with the DE@SiO2 system, the addition of Al(OH)3 in the DE@SiO2 / Al(OH)3 system can increase the tensile strength of the coating to 1.5 times that of the super-amphiphobic coating of the DE@SiO2 system by sacrificing only a small amount of elongation, proving that the addition of Al(OH)3 is beneficial to improving strength.
[0074] Figure 5 This is a physical picture of the super-amphiphobic porous powder suspension prepared in Example 3. Figure 5 It can be seen that the super-amphiphobic porous powder suspension is off-white. Figure 6 Characterization of wettability of several powders, including Figure 6 (a) From left to right are unmodified aluminum hydroxide nanoparticles, unmodified micron porous particles, and super-amphiphobic porous powder prepared in Example 3. On the surface of the super-amphiphobic porous powder, the dyed soybean oil is spherical, and the comparison between the unmodified aluminum hydroxide nanoparticles and the unmodified micron porous particles shows that the modified particles have excellent oleophobic properties. Figure 6(b) It shows that the super-amphiphobic porous powder prepared in Example 3 has excellent hydrophobic properties and has a clear boundary with water in the bottle. The super-amphiphobic porous powder prepared in Example 3 is diluted with ethanol at a mass ratio of 1:5 and sprayed on a metal or glass sheet. A super-hydrophobic surface with a contact angle of 165° and a rolling angle of 1° can be obtained.
[0075] Example 5
[0076] The super-amphiphobic porous powder prepared in Example 3 was used as a raw material to prepare a super-amphiphobic coating, specifically:
[0077] In terms of mass fractions, 0.15 parts of fluorocarbon surfactant FS-30 and 6 parts of super-amphiphobic porous powder were dispersed in 20 parts of deionized water, and then 20 parts of aqueous polyurethane resin were added. After stirring for 5 minutes, the coating of the porous powder was obtained. The coating of the porous powder was applied to any cleaned substrate surface, and the mixture was heated and dried in an oven at 150°C for 1 hour to obtain a super-amphiphobic coating.
[0078] Figure 7 The macroscopic wettability diagram of the coating is shown in Figure 1 for 5 μL water droplets and oil droplets. Figure 7 It can be seen that the rolling angles of water droplets and oil droplets are 1±0.3° and 1.5±0.5°. The super-amphiphobic coating has excellent super-hydrophobicity and super-oleophobicity, and its surface wetting state has reached the Cassie state. The coating has excellent uniformity and flatness, and there is no shrinkage, blistering, cracking, peeling, bottom exposure and other phenomena on the coating surface.
[0079] Example 6
[0080] The super-amphiphobic porous powder prepared in Example 3 was used as a raw material to prepare a super-amphiphobic coating, specifically:
[0081] In terms of mass fractions, 0.3 parts of super-amphiphobic porous powder were mechanically stirred and dispersed in 1.5 parts of butyl acetate, and then 0.5 parts of oily resin were added and stirred for 5 minutes to obtain a coating of the porous powder. The coating of the porous powder was applied to the surface of any cleaned substrate, and the coating was placed in an oven at 80°C for heating and drying for 1 hour to obtain a super-amphiphobic coating.
[0082] The prepared super-amphiphobic coating was cross-crossed by a paint film scribing device. Figure 8 The optical photos and schematic diagrams of the super-amphiphobic coating after scribbling. Figure 8 It can be seen that after the cross-cutting test, the coating did not fall off at all, and the coating adhesion was level 0. In addition, when water drops were dropped onto the super-amphiphobic coating after the cross-cutting test, the coating still maintained excellent super-hydrophobic properties after being scratched, and the coating showed excellent mechanical stability.
[0083] Example 7
[0084] The super-amphiphobic porous powder prepared in Example 3 was used as a raw material to prepare a super-amphiphobic coating, specifically:
[0085] By weight, 0.3 parts of super-amphiphobic porous powder were mechanically stirred and dispersed in 1.5 parts of butyl acetate, and then 0.5 parts of oily fluorocarbon resin were added. After stirring for 5 minutes, a coating of the porous powder was obtained. The coating of the porous powder was applied to any cleaned substrate surface and placed at room temperature for 5 to 10 minutes to obtain a super-amphiphobic coating.
[0086] The wear resistance of the coating was tested using the Taber test. The results are as follows: Fig. 9 The surface water contact angle of the coating is 152.05±1.08° and the rolling angle is 2.47±0.78°. After 1300r under a load of 1Kg, the water contact angle of the coating is still greater than 150°, as shown in Fig. 9 As shown in (a). Before the coating is worn, it presents a porous structure of loose overpasses. The micron particle skeleton is rich in modified nanoparticles. The synergistic effect of the structure and low surface energy substances makes the coating have excellent amphiphobicity, as shown in Fig. 9 (c) When the coating is worn, the micron-scale skeleton structure is flattened, but the nanoparticles can still be seen. This structure allows the coating to remain superhydrophobic after 1300r wear under a load of 1Kg, as shown in Fig. 9 (d) as shown.
[0087] Example 8
[0088] The super-amphiphobic porous powder prepared in Example 3 was used as a raw material to prepare a super-amphiphobic coating, specifically:
[0089] In parts by mass, 0.3 parts of super-amphiphobic porous powder were mechanically stirred and dispersed in 1.5 parts of butyl acetate, and then 0.5 parts of oily fluorocarbon resin and 0.15 parts of curing agent were added. After stirring for 5 minutes, the coating of the porous powder was obtained. The coating of the porous powder was sprayed onto the cleaned tinplate surface and placed at room temperature for 5 to 10 minutes to obtain a super-amphiphobic coating.
[0090] The super-amphiphobic coating was tested by a pulling experiment. The test results before and after pulling are as follows: Fig.10 As shown, the average adhesion of the coating with a film thickness of 160 μm is 6.05 MPa.
[0091] Example 9
[0092] The super-amphiphobic porous powder prepared in Example 3 was used as a raw material to prepare a super-amphiphobic coating, specifically:
[0093] In parts by mass, 0.3 parts of super-amphiphobic porous powder were mechanically stirred and dispersed in 1.5 parts of butyl acetate, and then 0.5 parts of oily fluorocarbon resin and 0.15 parts of curing agent were added. After stirring for 5 minutes, the coating of the porous powder was obtained. The coating of the porous powder was sprayed onto the surface of a cleaned glass substrate and placed at room temperature for 5 to 20 minutes to obtain a super-amphiphobic coating.
[0094] The antifouling effect of the coating was tested using cement slurry. The results are as follows: Fig.11 As shown in the figure, in the antifouling test, cement slurry can easily roll off the coating, and no trace of cement slurry is left on the white coating, indicating that the super-amphiphobic coating has excellent antifouling potential. The dust-proof effect of the coating was tested using soil, and the results are as follows: Fig.12 As shown in the dustproof test, dust can easily roll off the coating and no trace of dust is left on the white coating, indicating that the super-amphiphobic coating has excellent dustproof potential.
[0095] Example 10
[0096] The super-amphiphobic porous powder prepared in Example 3 was used as a raw material to prepare a super-amphiphobic coating. Specifically, 1 part of the super-amphiphobic porous powder was evenly mixed with 30 parts of polyester resin powder by a dry mixing method to obtain a mixed powder. The mixed powder was sprayed onto a conductive substrate by an electrostatic powder spraying method, baked at 110-150°C for 30 minutes, and cured at 180-250°C for 15 minutes to obtain a coating with anti-concrete properties.
[0097] The self-cleaning performance of the coating was tested using cement ash, such as Fig.13 As shown in (a), the cement dust on the coating can be easily removed by washing with deionized water. The antifouling effect of the coating was tested using cement slurry. Fig.13 As shown in (b), in the antifouling test, large pieces of mortar can be easily removed from the coating, and no traces of mortar are left on the uniform and dense coating, indicating that the powder coating has excellent antifouling potential.
[0098] In addition, the hydrophobic and anti-concrete capabilities of powder coatings with different ratios were quantitatively characterized experimentally, and the results are shown in Fig.13 As shown in (c), the coating obtained when the mass ratio of super-amphiphobic porous powder to resin powder is 1:50 has the best anti-concrete ability.
Claims
1. A method for preparing a super-amphiphobic porous powder, characterized in that: The steps include: (1) In a constant temperature water bath at 50-80°C, 0.3-0.5 parts of a surfactant, 5-8 parts of a nanosol, 4-5 parts of ammonia water, and 0.4-0.5 parts of a low surface energy substance are added to water, and stirred to obtain a modified nanoparticle suspension; (2) adding 0.5-0.6 parts of a low surface energy substance, 0.7-1.2 parts of aluminum hydroxide and 3-5 parts of micron porous particles to the nanoparticle suspension in sequence, and stirring to obtain a micron porous particle suspension loaded with nanoparticles; the micron porous particles are at least one of ceramic, diatomaceous earth or glass porous microspheres with a particle size of 10-50 μm; (3) The micron porous particle suspension is dried at high temperature to obtain a super-amphiphobic porous powder loaded with nanoparticles.
2. The method for preparing a super-amphiphobic porous powder according to claim 1, characterized in that: In step (1), the surfactant is at least one of FS-3100, FS-61 or FS-30.
3. The method for preparing super-amphiphobic porous powder according to claim 1, characterized in that: In step (1), the nanosol is one of zinc oxide, silicon dioxide and titanium dioxide with a particle size of 5 to 40 nm, the nanosol has a solid content of 10 wt.% to 35 wt.%, and a pH value of 9 to 12.
4. The method for preparing super-amphiphobic porous powder according to claim 1, characterized in that: In step (1) and step (2), the low surface energy substance is at least one of tridecafluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane or tridecafluorooctyltrimethoxysilane.
5. The method for preparing super-amphiphobic porous powder according to claim 1, characterized in that: In step (3), the drying temperature is 120-180° C., and the drying time is 4-6 h. The particle size of the super-amphiphobic porous powder loaded with nanoparticles is 10-80 μm.
6. A water-based coating containing the super-amphiphobic porous powder prepared by the method of claim 1, characterized in that: The invention comprises the following components in parts by weight: 1.5 to 2 parts of super-amphiphobic porous powder, 0.15 parts of surfactant, 3 to 5 parts of film-forming material and 9 to 10 parts of deionized water; the film-forming material is at least one of a low-surface-energy water-based fluorocarbon resin, a water-based acrylic resin or a water-based polyurethane resin, a silicone resin or an epoxy resin; the surfactant is at least one of FS-3100, FS-61 or FS-30.
7. An oily paint containing the super-amphiphobic porous powder prepared by the method of claim 1, characterized in that: The invention comprises the following components in parts by weight: 0.1-0.5 parts of super-amphiphobic porous powder, 0.5-0.6 parts of oily resin and 1-2 parts of organic solvent; the organic solvent is at least one of butyl acetate, ethanol, n-hexane, ether, benzene or ketone.
8. A powder coating containing the super-amphiphobic porous powder prepared by the method of claim 1, characterized in that: The invention comprises the following components in parts by weight: 0.2 to 1 parts of super-amphiphobic porous powder and 6 to 30 parts of binder powder; the binder powder is at least one of polyester resin powder, polymethyl methacrylate powder or polytetrafluoroethylene resin powder.